When Do Patients with Breast Cancer Seek Help from Psycho-oncology Services? A 3-Year Retrospective Study from India - Arnab Mukherjee; Bidisha Samanta; Varuna Sharma; Aagon Krishna Shrestha; Shreshta Chattopadhyay; Chitralekha Bhowmick; Joydeep Ghosh; Sandip Ganguly; Sanjit Kumar Agrawal; Soumitra Shankar Datta (Indian Journal of Medical and Paediatric Oncology)
Introduction Breast cancer is the most frequent cancer among women. In the last few decades, the outcome of breast cancer has improved significantly in terms of survivorship and quality of life. However, it is crucial that alongside managing the disease, breast cancer services address and manage associated or co-occurring psychiatric illnesses such as acute stress reactions, procedural anxieties, adjustment issues, depression, and fear of recurrence, which leads to an overall better experience of the patient.